Exploring the Spatial Potential of Loose Space as Urban Pores in Tunjungan Street - Ribka Irena Kartowidjojo; Liliany Sigit Arifin (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2026)
The phenomenon of urban canyons, characterized by narrow street corridors flanked by dense vertical building masses, has emerged in many city centers, including the Tunjungan (CBD) in Surabaya, resulting in a decline in environmental quality and pedestrian comfort. This study aims to explore the spatial potential of loose spaces, defined as remaining or underutilized urban spaces, as potential urban pores in the context of dense urban canyons. A descriptive qualitative approach was used through direct field observations and visual documentation. Six loose space locations along the Tunjungan corridor were selected and analyzed using six qualitative parameters derived from the theory of loose spaces and urban porosity, adapted to local conditions. The findings indicate that several loose spaces possess spatial characteristics that indicate ecological and social potential, particularly in relation to spatial openness and opportunities for social interaction. This study positions loose spaces as an initial spatial resource that can inform future urban strategies that help address urban canyon conditions in urban areas.